Pengaruh Spiritualitas di Tempat Kerja terhadap Turnover Intention Perawat melalui Komitmen Organisasional di Rumah Sakit Islam Unisma Malang - Budiono, Sugeng; Alamsyah, Arief; Noermijati (Jurnal Aplikasi Manajemen, 2014)
The aim of this study was to examine the influence of spirituality in the workplace against the turnover intention of nurses through organizational commitment. This study used an explanatory research design with cross sectional approach. The sample was nurses who have been working for over a year in the Islamic Hospital Unisma Malang with total 89 nurses. The sampling method used the total population (census). The results of hypothesis testing using path analysis showed that spirituality in the workplace has a positive effect on organizational commitment to perform, organizational commitment negatively affect turnover intention, spirituality in the workplace negatively affect the turnover intention of nurses and spirituality in the workplace indirect effect on turnover intention of nurses through a commitment organizational.